Case reportFlagellate dermatitis after consumption of Shiitake mushrooms - Czarnecka, Agnieszka B.; Kreft, Burkhard; Marsch, Wolfgang Ch. (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Flagellate dermatitis occurs in patients who have eaten Shiitake mushrooms. We are reporting on a 55-year-old man, who developed whiplash-striped, severely itching efflorescences on the trunk 3 days after eating Lentinula edodes. Flagellate dermatitis is also known as a cutaneous side effect of bleomycin therapy.